Longitudinal evaluation of the frequency of sexual intercourse and sexual activity in patients after nerve‐sparing robot‐assisted laparoscopic radical prostatectomy. (27th December 2020) - Inoue, Shogo; Hayashi, Testutaro; Teishima, Jun; Matsubara, Akio
Abstract : Objective: To evaluate the frequency of sexual intercourse and sexual activity of patients after nerve‐sparing (NS) robot‐assisted laparoscopic radical prostatectomy (RARP). Patients and Methods: We prospectively obtained 2‐years longitudinal Expanded Prostate Cancer Index Composite (EPIC) and Sexual Health Inventory for Men (SHIM) score data from 99 patients. We classified the frequency of sexual intercourse and sexual activity as 'none', 'less than once a week', 'about once a week', 'several times a week', and 'daily'. Results: The percentages of patients who took part in sexual activity before and at 3, 6, 9, 12, 18, and 24 months after NS RARP were 55.6%, 27.9%, 38.8%, 42.5%, 44.4%, 41.7%, and 42.1%, respectively. The percentages of patients who took part in sexual intercourse before and at 3, 6, 9, and 12, 18, and 24 months after NS RARP were 41.4%, 9.0%, 13.3%, 16.3%, 16.7%, 22.2%, and 23.7%, respectively. Preoperative sexual status was classified into two groups: those who had sexual intercourse or those who only had sexual activity except sexual intercourse. Sexual function (SF) was investigated longitudinally using the EPIC and SHIM data between the two groups. The SHIM data showed an improvement in SF in the sexual intercourse group, but did not do so in the sexual activity except sexual intercourse group. On the other hand, SF in the EPIC data might reflect the postoperative improvement of SF in the sexual activity except sexual intercourse group. Conclusion: There was a large discrepancy between the percentages of patients taking part in sexual intercourse and sexual activity; therefore, surveys of postoperative SF are recommended to include not only sexual intercourse but also sexual activity.